2022
DOI: 10.1002/jts.22827
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics, torture experiences, and posttraumatic stress disorder symptoms among asylum seekers and refugees persecuted for same‐sex behaviors

Abstract: Increasingly, lesbian, gay, and bisexual (LGB) individuals are fleeing the 67 countries that criminalize consensual same‐sex intimate relationships, seeking asylum in countries such as the United States. Minority stress theory posits that compared with non‐LGB refugees and asylum seekers (RAS), LGB RAS are likely to face persecution, rejection, and discrimination and have a higher risk of experiencing posttraumatic stress disorder (PTSD) symptoms. This study assessed differences in sociodemographic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The experiences of this study's participants were consistent with research showing that abuses experienced by LGBTQ+ asylum seekers often begin in youth (Shidlo & Ahola, 2013) and can contribute to significant psychological distress (Bird et al., 2022). The earliest ill treatment participants reported experiencing was often associated with family and community rejection or violence.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The experiences of this study's participants were consistent with research showing that abuses experienced by LGBTQ+ asylum seekers often begin in youth (Shidlo & Ahola, 2013) and can contribute to significant psychological distress (Bird et al., 2022). The earliest ill treatment participants reported experiencing was often associated with family and community rejection or violence.…”
Section: Discussionsupporting
confidence: 84%
“…The earliest ill treatment participants reported experiencing was often associated with family and community rejection or violence. Furthermore, due to a potential lack of affirming family relationships, LGBTQ+ asylum seekers may be isolated from typical networks of support once in the United States (Bird et al., 2022; Shidlo & Ahola, 2013; Redcay et al., 2019), which may contribute to housing instability or disrupt their paths to citizenship within the family‐centric structure of U.S. immigration policy (Collier & Daniel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A particularly vulnerable subgroup of RAS appears to be RAS who identify as a sexual minority (SM) individual and/or RAS who have been persecuted for engaging in romantic, consensual same-sex acts (hereinafter identified as sexual minority refugees and asylum seekers [SM RAS] Bird et al, 2022;Fox et al, 2020;Piwowarczyk et al, 2017); a population increasing in number in the United States (U.S., Williams Institute-University of California Los Angeles [UCLA] School of Law, 2021). While research is scant on this population, recent studies have demonstrated that SM RAS experience higher rates of trauma than those persecuted for reasons other than their sexual identity or for engaging in romantic, consensual same-sex acts (e.g., political, religious; hereinafter referred to as non-SM RAS; Bird et al, 2022;Piwowarczyk et al, 2017). Unlike non-SM RAS, SM RAS carry the additional burden of having experienced identityrelated trauma due to their sexual orientation via oppressive, majority systems, as outlined by minority stress theory (MST; Brooks, 1981;Meyer, 2003).…”
mentioning
confidence: 99%
“…Refugees and asylum seekers (RAS) are vulnerable to experiencing traumatic events (e.g., resource restriction, punishment, torture, prejudice, alienation, and imprisonment) at all stages of migration (Theisen-Womersley, 2021). Indeed, most RAS experience some form of trauma, often seeking protection from persecution and discrimination based on their race, gender, sexual orientation, and political and religious affiliations (Bird et al, 2022; Pittaway & Bartolomei, 2001; Šorytė, 2018). In their countries of asylum, RAS may face additional oppression-based stressors such as navigating societal biases and identity-based discrimination (Adida et al, 2019).…”
mentioning
confidence: 99%
“…Sexual and gender minority (SGM) people, including agender, asexual, bisexual, gay, gender diverse, genderqueer, genderfluid, intersex, lesbian, nonbinary, pansexual, queer, and transgender people and others who are not cisgender and/or heterosexual (Table 1 for definitions), experience stigma and structural discrimination. [1][2][3][4][5][6][7] These experiences have a profound impact on health, health care seeking, and health care experiences. [8][9][10] At least 7% of U.S. adults self-report SGM identities, 1% as lesbians, 1% as gay, 4% as bisexual, and 1% as transgender.…”
mentioning
confidence: 99%